Dark as night: Spelunking for spinal solitary fibrous tumors/hemangiopericytomas in the differential of T2 hypointensity. (August 2020) - Carlstrom, Lucas P.; Graffeo, Christopher S.; Perry, Avital; Atkinson, John D.; Lanzino, Giuseppe; Meyer, Fredric B.; Morris, Jonathan M.
Highlights: T2 hypointensity may be a predictor of indolence in SFT/hemangiopericytomas. T2 hypointense spinal lesions are rare, encompassing an array of diseases. Review identified T2 hypointensity in 16 focal, 5 diffuse, and 4 mixed lesions. Abstract: Spinal solitary fibrous tumor/hemangiopericytoma (SFT/HPC) is a rare mesenchymal malignancy. Radiographically, SFT/HPCs have a mutable appearance, with irregular borders, heterogeneous contrast enhancement, and variable but frequently hypointense T2 signal. We report a series of 5 neurosurgically managed spinal SFT/HPCs treated at our institution, with particular attention to 3 lesions demonstrating marked T2-hypointensity and differential diagnosis for the unusual finding of a "T2 dark" spinal lesion. Retrospective chart review of prospectively maintained surgical database, queried by diagnosis and site codes, 2002–2017. Retrospective radiographic review, with initial screening via keyword search of MR reports for "T2" and "hypointense." Four primary and one metastatic spinal SFT/HPCs were operatively treated during the study period (median follow-up 12 months; range 10–92). Three demonstrated marked T2 hypointensity on preoperative MRI, underwent primary resection—GTR in two, STR in one—and have remained progression-free on routine postoperative surveillance. Two patients with isointense lesions recurred within the follow-up period. Radiographic review identified a host of predominantly rare T2-hypointense lesions, including arteriovenous malformation, disk fragmentations, calcific arachnoiditis, calcifying pseudoneoplasm of the neuraxis, cavernoma, cord hemorrhage/acute blood, desmoid, granulocytic sarcoma, pigmented villonodular synovitis, Edheim-Chester, extramedullary hematopoiesis, IgG4-negative inflammatory pseudotumor, idiopathic hypertrophic pachymeningitis, B-cell lymphoma, primary melanoma neoplasm, melanotic schwannoma, meningioma, opacification of the posterior longitudinal ligament, osteoblastoma, osteochondroma, osteosarcoma, and synovial cyst. T2 hypointensity is associated with SFT/HPC, and may be an indicator relative indolence. "Dark" T2 spinal lesions are rare, with a narrow differential populated predominantly by rare entities.